Foreign Entanglements : Estimating the Source and Size of Spillovers Across Industrial Countries - Bayoumi, Tamim (IMF Working Papers; Working Paper, 2007)
VARs of real growth since 1970 are used to estimate spillovers between the U.S., euro area, Japan, and an aggregate of small industrial countries, which proxies for global shocks. U.S. and global shocks generate significant spillovers, while those from the euro area and Japan are small. This paper also calculates the standard errors of impulse-response functions including uncertainty over the proper Cholesky ordering. Extensions adding real net exports, commodity prices, and financial variables indicate that financial effects dominate spillovers. The results by subperiod underline the importance of the great moderation in U.S. output fluctuations and associated financial stability in lowering output volatility elsewhere.